2016
DOI: 10.1186/s12907-016-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of placental morphology may identify specific causes of stillbirth

Abstract: BackgroundStillbirth is frequently the result of pathological processes involving the placenta. Understanding the significance of specific lesions is hindered by qualitative subjective evaluation. We hypothesised that quantitative assessment of placental morphology would identify alterations between different causes of stillbirth and that placental phenotype would be independent of post-mortem effects and differ between live births and stillbirths with the same condition.MethodsPlacental tissue was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…At a microscopic level, trophoblast proliferation is reduced and the presence of syncytial nuclear aggregates (also termed syncytial knots) in increased (17). These changes are also seen in post-term pregnancies and in FGR stillbirths (21)(22)(23), thus these observations are consistent with a hypothesis of accelerated placental ageing in mothers ≥35 years of age, which could explain the increased risk of stillbirth from 40 weeks' gestation seen at 42 weeks' gestation in women <35 years of age (9).…”
Section: Evidence From Basic Science Studies Of Amasupporting
confidence: 73%
“…At a microscopic level, trophoblast proliferation is reduced and the presence of syncytial nuclear aggregates (also termed syncytial knots) in increased (17). These changes are also seen in post-term pregnancies and in FGR stillbirths (21)(22)(23), thus these observations are consistent with a hypothesis of accelerated placental ageing in mothers ≥35 years of age, which could explain the increased risk of stillbirth from 40 weeks' gestation seen at 42 weeks' gestation in women <35 years of age (9).…”
Section: Evidence From Basic Science Studies Of Amasupporting
confidence: 73%
“…The pathologic processes implicated in fetal death include: infection 6584 , placental abruption, 5, 37, 70, 8592 vascular lesions of the placenta, 28, 35, 93100 preeclampsia, 41, 101105 fetal growth restriction 9, 106114 , maternal anti-fetal rejection, 35, 115120 metabolic disorders, 121133 genetic disorders, 80, 131, 134137 umbilical cord accident, 97, 138145 trauma 146148 , and placental senescence 22 ; however, most of the 47,000 stillbirths reported from developed countries in 2015 149 were classified as unknown etiology. It is currently believed that the causes of fetal loss change with gestational age: chromosomal abnormalities 150153 and infection 75 are the most common causes during the first half of pregnancy, placental causes (abruption or vascular abnormalities) 154156 , and maternal anti-fetal rejection 118 become the most common causes after 26 weeks until term 14 , after which the etiology of in most cases, especially after 40 weeks, is unknown 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst previous studies have reported on placental findings in autopsies following intrauterine death, our current findings are based on a large dataset with predefined objective criteria for classification of cause of death. This dataset also allows exploration of the relationship between gestational age, across the full range of second‐ and third‐trimester intrauterine deaths, and placental findings.…”
Section: Discussionmentioning
confidence: 99%
“…Improved understanding of the mechanisms of intrauterine death require scientifically rigorous, objective criteria in order to separate truly pathological placental findings from incidental features that may overlap extensively with those of normal populations. Recent research demonstrates that a quantitative approach to placental morphology and placentally derived hormones may help to better identify lesions of pathological significance.…”
Section: Discussionmentioning
confidence: 99%